Timelike and spacelike hadron form factors, Fock state components and light-front dynamics - Pace, E.; Salme, G.; Frederico, T.; Pisano, S.; de Melo, J. P. B. C. (Elsevier B.V., 2007)
A unified description of spacelike and timelike hadron form factors within a light-front model was successfully applied to the pion. The model is extended to the nucleon to study the role of qq pair production and of nonvalence components in the nucleon form factors. Preliminary results in the spacelike range 0 <= Q(2) <= 10 (GeV/c)(2) are presented.